Áp dụng lý thuyết đổi mới trong quản lý giá trị - kho hàng hóa - Hy, Nguyen Quy; Lam, Le Xuan (Journal of Computer Science and Cybernetics, 2018)
In this paper, by the general theory, a method to predict of items which character to value goods are managed by warehousemen is demonstrated. They must be choose the optimal time for the put and sell a lot of goods at their godown. By Turbo Pascal V.5 on IBM PC AT we outperform those results.